Indefinite integral...(1)

Calculus Level 3

Evaluate ( x 4 x ) 1 / 4 x 5 d x \large \int\frac{(x^4-x)^{1/4}}{x^5} dx

Problem is not orignal.

4 13 ( 1 1 x 4 ) 5 / 4 + C \frac{4}{13}\left(1-\frac{1}{x^4}\right)^{5/4}+C 4 13 ( 1 + 2 x 3 ) 5 / 4 + C \frac{4}{13}\left(1+\frac{2}{x^3}\right)^{5/4}+C 4 15 ( 1 1 x 3 ) 5 / 4 + C \frac{4}{15}\left(1-\frac{1}{x^3}\right)^{5/4}+C 4 15 ( 1 1 x 3 ) 3 / 4 + C \frac{4}{15}\left(1-\frac{1}{x^3}\right)^{3/4}+C

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Satyendra Kumar
Dec 13, 2014

Dividing numerator and denominator by x 5 x^5 ,we get, ( x 4 x 20 x x 20 ) 1 4 d x \int(\dfrac{x^4}{x^{20}}-\dfrac{x}{x^{20}})^\frac{1}{4}dx = ( x 16 x 19 ) 1 4 d x =\int(x^{-16}-x^{-19})^\frac{1}{4}dx = x 4 ( 1 x 3 ) 1 4 d x =\int x^{-4}(1-x^{-3})^{\frac{1}{4}}dx Now,substituting 1 x 3 = z 1-x^{-3}=z we get, x 4 d x = 1 3 d z . x^{-4}dx=\dfrac{1}{3}*dz. The integral now becomes, = 1 3 z 1 4 d z =\int\dfrac{1}{3}*z^{\frac{1}{4}}dz = z 5 4 4 5 1 3 =z^{\frac{5}{4}}*\dfrac{4}{5}*\dfrac{1}{3} = 4 15 ( 1 x 3 ) 5 4 . =\dfrac{4}{15}*(1-x^{-3})^{\frac{5}{4}}.

Perfect solution

Aman Sharma - 6 years, 6 months ago

I = ( x 4 x ) 1 4 x 5 d x = ( x 4 x 20 x x 20 ) 1 4 d x = ( x 16 x 19 ) 1 4 d x = x 4 ( 1 x 3 ) 1 4 d x \begin{aligned} I & = \int \frac {(x^4-x)^\frac 14}{x^5} dx \\ & = \int \left(\frac {x^4}{x^{20}} -\frac x{x^{20}} \right)^\frac 14 dx \\ & = \int \left(x^{-16} - x^{-19} \right)^\frac 14 dx \\ & = \int \color{#3D99F6}{x^{-4} \left(1- x^{-3} \right)^\frac 14} dx \end{aligned}

Now, note that d d x ( 1 x 3 ) 5 4 = 5 4 ( 1 x 3 ) 1 4 3 x 4 = 15 4 x 4 ( 1 x 3 ) 1 4 \dfrac d{dx} \left(1- x^{-3} \right)^\frac 54 = \dfrac 54 \left(1- x^{-3} \right)^\frac 14 \cdot 3x^{-4} = \dfrac {15}4 \color{#3D99F6}{x^{-4} \left(1- x^{-3} \right)^\frac 14} .

I = 4 15 ( 1 1 x 3 ) 5 4 + C \implies I = \boxed{\dfrac 4{15} \left(1- \dfrac 1{x^3} \right)^\frac 54 + C}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...